Toys from childhood in immigration: placing memories into context - Protassova, Ekaterina; Yelenevskaya, Maria (Frontiers in Psychology, 2025)
IntroductionAmong the first objects which babies view and watch are various toys. The play has an enduring impact for the personal growth. The goal of our project was to explore why toys and playthings brought from the country of origin are an important component of the material and symbolic heritage in diasporic Russophone families, how their meaning is negotiated, and values assigned.Materials and methodsThe study uses thematic, discourse, and content analysis drawing on a survey and group interviews. The participants (53 + 25), aged 5–61 at the time of relocation, emigrated from Russia and other post-Soviet countries to various destinations for personal, family, and professional reasons.Results and discussionThe results of the survey we conducted emphasize the multifaceted role of toys in child development, family culture, and education, stressing the importance of play over the toys themselves. Respondents advocate a thoughtful curation of toys to foster creativity and emotional growth, noting that an excess of toys may hinder children’s imagination. Psychologically, toys provide comfort, joy, and a sense of continuity amidst transitions. Families value traditional or handmade toys for their cultural and historical significance, creativity enhancement, emotional connections, and intergenerational bonding in the language transmission. The independent play fosters processing of emotions and transitions from life in a familiar milieu to a new environment. Environmental concerns about plastic toys and a preference for sustainable materials are raised. Participants view toys as contributors to children’s integration into the host society. The detailed personal narratives of those who migrated at an early age focus on the toys that shaped their early years revealing a profound significance of playthings, reflecting on the creativity and resourcefulness in their play and witnessing diverse economic circumstances and cultural backgrounds.ConclusionParticipants’ memories and experiences with toys show how language serves as a crucial medium for expressing and preserving memories, while culture provides the context within which these toys are understood and valued. Social interactions and cultural norms impact the significance of toys in the lives of the Russophone immigrants.